Tracking control of a large range 3D printed compliant nano-manipulator with enhanced anti-windup compensation. (15th September 2019) - Cui, Mengjia; Zhang, Zhen; Yan, Peng
Highlights: Large range compliant nano-stage of spatial constraint restrain parasitic rotation. IMP-based control and enhanced antiwindup for tracking and saturation compensation. Control of 3D printed manipulator showing significant reduced error in saturation. Abstract: This paper studies tracking of a large stroke 3D printed XY compliant nano-manipulator with spatial constraints. To asymptotically track periodic references, an internal model principle-based control is utilized as the baseline tracking controller. To avoid the actuator input saturation in relatively large stroke, an enhanced anti-windup scheme with an integrated compensation strategy is developed, where the anticipatory anti-windup compensator and the conventional one are adopted in different operation modes. The design of the modified anti-windup compensator is decoupled with the internal model principle-based controller to facilitate the integrated control design. The synthesis of linear matrix inequality (LMI) is also provided to obtain the parameters of the dynamic anti-windup compensator. The proposed control strategy is experimentally validated, where the tracking error is 62.54  nm (RMS) in absence of saturation and significant error reduction in the presence of saturation is demonstrated compared with the conventional anti-windup compensation.